Rose (Rosa gallica) Petal Extract Suppress Proliferation, Migration, and Invasion of Human Lung Adenocarcinoma A549 Cells through via the EGFR Signaling Pathway - Won-Chul Lim; Hyo-Kyung Choi; Kyung-Tack Kim; Tae-Gyu Lim (Molecules, 2020)
We sought to investigate the effect of rose petal extract (RPE) on the proliferation, migration, and invasion of cancer cells. RPE significantly inhibited the growth of lung and colorectal cancer cell lines, with rapid suppression of A549 lung cancer cells at low concentrations. These effects occurred concomitantly with downregulation of the cell proliferation mediators PCNA, cyclin D1, and c-myc. In addition, RPE suppressed the migration and invasion of A549 cells by inhibiting the expression and activity of matrix metalloproteinase-2 and matrix metalloproteinase-9 (MMP-2 and -9). We hypothesize that the suppressive activity of RPE against lung cancer cell proliferation and early metastasis occurs via the EGFR-MAPK and mTOR-Akt signaling pathways. These early results highlight the significant potency of RPE, particularly for lung cancer cells, and warrant further investigation.